Fundamental Study for a Graphite-Based Microelectromechanical System - Sone, Junji; Murakami, Mutsuaki; Tatami, Atsushi (Micromachines (Basel), 2018)
We aimed to develop a process for constructing a carbon-based microelectromechanical system (MEMS). First, we prepared a highly oriented pyrolytic graphite (HOPG) crystal microsheet by exfoliation. We fabricated cantilevers and a double-clamped beam by controlling the thickness of the HOPG microsheet using a MEMS process. Second, we used a graphite sheet with contour line adhesion by metal sputter deposition. Third, we used a highly accurate graphite sheet with face adhesion and laser cutting. The first resonance frequencies were evaluated. We confirmed improvement in Q values to 1/10 level of a quarts vibrator, high performance, and a simple structure.